A note concerning government bond yields - Tanweer Akram (Levy Economics Institute of Bard College, 2020)
This paper relates Keynes's discussions of money, the state theory of money, financial markets, investors' expectations, uncertainty, and liquidity preference to the dynamics of government bond yields for countries with monetary sovereignty. Keynes argued that the central bank can influence the long-term interest rate on government bonds and the shape of the yield curve mainly through the short-term interest rate. Investors' psychology, herding behavior in financial markets, and uncertainty about the future reinforce the effects of the short-term interest rate and the central bank's monetary policy actions on the long-term interest rate. Several recent empirical studies that examine the dynamics of government bond yields substantiate the Keynesian perspective that the long-term interest rate responds markedly to the short-term interest rate. These empirical studies not only vindicate the Keynesian perspective but also have relevance for macroeconomic theory and policy.
Keywords: E12; E40; E43; E50; E58; E60; F30; G10; G12; H62; H63; 330; Money; State Theory of Money; Chartalism; Monetary Theory; Central Bank; Government Bond Yields; Interest Rate; John Maynard Keynes